Part I: Tungsten-catalyzed cyclization of alkyne derivatives. Part II: Palladium-catalyzed C-H bond functionalization of benzylic phosphonic monoesters - Meng, Xiangjian (2014)
The work of this thesis has been directed towards the development of tungsten-catalyzed chemistry in the transformation of alkyne derivatives, and palladium-catalyzed functionalization of benzylic phosphonic monoesters via C−H activations. This thesis is divided into two parts: Part I is aimed at exploring novel approaches for the synthesis of heterocycles via cylization of alkyne derivatives employing tungsten catalysis. Chapter 1 gives an introduction to tungsten catalysis and its application in the formation of heterocycles via cyclization of alkyne derivatives. Chapter 2 describes the tungsten-catalyzed cyclization of N-propargylic amides to afford the corresponding oxazolines or oxazines via 5-exo-dig or 6-endo-dig mode. Chapter 3 details the tungsten-catalyzed cyclization of α-alkynyl-β-keto acids, keto esters, and diketones to afford methylenelactones, furans, and methylenecyclopentanes via 5-exo-dig cyclization under photo conditions. Also, the present approach could be further applied to 5-endo-dig cyclization. In addition, pyrroles, pyridines and isoquinolines were also efficiently synthesized via cyclization of alkyne derivatives tethered to nitrogen nucleophiles under thermal conditions in the presence of tungsten catalysis. Part II is aimed at exploring phosphoryl-related directing groups-assisted C−H activation reactions employing palladium catalysis. Chapter 4 gives an introduction of palladium-catalyzed directing-group-assisted olefination and arylation of aryl C−H bonds in recent decades and a brief discussion of related mechanisms. In Chapter 5, the new monophosphonic acid directing group was successfully utilized in the Pd(II)-catalyzed ortho-olefination and acetoxylation of benzylic phosphonic monoesters. The synthetic utility of ortho-olefination was exemplified by the application of the newly formed olefinated products in Horner-Wadsworth-Emmons reactions. In Chapter 6, the new mono-phosphonic acid-directing group was successfully utilized in the Pd(II)-catalyzed ortho-arylation of benzylic phosphonic monoesters with potassium aryltrifluoroborates. A wide range of benzylic phosphonic monoesters underwent clean ortho-arylation in high yields and excellent functional group tolerance was also observed. The newly formed arylated products were also successfully applied in Horner-Wadsworth-Emmons reactions. The success of the work in Chapter 4 and 5 offers further development of other phosphoryl-related directing groups in the transition-metal-catalyzed C−H activations.